RETRACTED: Recent Trends, Challenges, and Future Aspects of P2P Energy Trading Platforms in Electrical-Based Networks Considering Blockchain Technology: A Roadmap Toward Environmental Sustainability - Javed, Haseeb; Irfan, Muhammad; Shehzad, Moazzam; Abdul Muqeet, Hafiz; Akhter, Jumshed; Dagar, Vishal; Guerrero, Josep M. (Frontiers in Energy Research, 2022)
Peer-to-peer (P2P) energy trading platform is an upcoming energy generations and effective energy managing strategy that rewards proactive customers (acting as prosumers) in which individuals trade energy for products and services. On the other hand, P2P trading is expected give to multiple benefits to the grid in minimizing the peak load demand, minimizing energy consumption costs, and eliminating network losses. However, installing P2P energy trading on a broader level in electricity-based networks present a number of modelling problems in physical and virtual network layers. As a result, this article presents a thorough examination for the literature of P2P studies of energy trade. In this research, an overview is given with the essential characteristics of P2P energy trading and comparatively analyze with multiple advantages for the utility grid and individual prosumers. Therefore, the studies then address in the physical and virtual levels in which categorize the available research systematically. Further, the technological techniques have been gone through multiple problems that needs to overcome for P2P energy trading in electrical networks. Finally, the article concludes with suggestions for further research.